Exstrophy epispadias complex with adenocarcinoma in adults: a case series and repair technique - Ranjan, Amit; Sarma, Debanga; Barua, Sasanka Kumar; Phukan, Mandeep; Bagchi, Puskal Kumar (International Surgery Journal, 2023)
The exstrophy-epispadias-complex (EEC) is a rare congenital malformation with a spectrum of abdominal-pelvic fusion abnormalities, with an incidence of 1/46,000 LB. Recurrence is 1 in100 & the male-to-female ratio is 2.3:1. Patients rarely may present in adulthood due to a lack of knowledge or financial constraints; it increases the risk of bladder carcinoma mostly adenocarcinoma or squamous carcinoma, due to chronic inflammation, infection, and metaplasia. It has a significant physical, functional, social, sexual, and psychological burden. Three patients have been operated on in our institute. A 37-year-old male, A 19-year-old male, and A 23- year-old female patient. The operation planned was a radical cystectomy with an ileal conduit and an expanded local lymphadenectomy in all three patients. The pelvis and abdominal wall defects were repaired differently post-radical cystectomy in all 3 patients using different techniques. The first patient went through primary tension closure, in the second patient bilateral rectus muscle was used as a flap and reinforced with mesh, and in the third patient, we used a rotation skin flap. All three patients were followed for 1 year. The first patient developed wound dehiscence followed by fecal fistula during follow-up and succumb due to sepsis, the second patient recovered well with a muscle flap in the postoperative period, unfortunately, developed recurrence locally and succumb due to multiple metastases, and the third patient develops flap necrosis at the tip postoperative on day 5, however, recover well after dressing, no recurrence seen on 1 year of regular follow up. As a result, the bilateral rectus flap with mesh recovers better than the rotation skin flap, which is better than primary tension closure.